Wireless Valley, Silicon Wadi and Digital Island - Helsinki, Tel Aviv and Dublin in the ICT Boom - Stephen Roper; Seamus Grimes (European Regional Science Association (ERSA), 2003)
In the context of the global production network (GPN) paradigm, this paper considers the combination of local and global factors which have contributed to the development of the ICT clusters in three small countries. Developments in each country reflect the combination of local advantages in human, knowledge and institutional capital and each nation's global economic and socio-political linkages. A key focus of the paper is the role of each nation's capital city - or more accurately the capital city region - in the development of the ICT cluster. The consequences for the regional distribution of ICT activity within the three countries are discussed, along with the potential technological and competitive implications of this distribution. Initial sections of the paper focus on the factors which underpinned the massive growth of the ICT sector in each country in the latter half of the 1990s. This leads to an assessment of the global market position of each industry and its prospects in any future upturn. The paper considers different aspects of the role of Tel Aviv, Dublin and Helsinki in attracting and supporting ICT development are considered. Symbolic and image factors are considered in terms of the cities' ability to attract internationally mobile human and financial capital. Institutional (e.g. higher education, thickness of financial institutions) and infrastructural factors are also considered in terms of the cities' ability to support and facilitate ICT companies. The role of entrepreneurship is also considered alongside the availability of venture capital etc.
Keywords: 330